The power of coarse graining in biomolecular simulations. (27th August 2013) - Ingólfsson, Helgi I.; Lopez, Cesar A.; Uusitalo, Jaakko J.; de Jong, Djurre H.; Gopal, Srinivasa M.; Periole, Xavier; Marrink, Siewert J.
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>